FUN LEARNING DURING RAMADHAN BY USING ONCE UPON A TIME CARD IN TEACHING NARRATIVE - Sari, Dian Purnama (TELL - US JOURNAL, 2022)
The purpose of this research is to teach English through a fun and dynamic activity during Ramadhan by using Once Upon a Time card. This learning activity was a part of an effort to increase students’ motivation to speak English in the classroom. This study was investigated through descriptive qualitative research where the researcher using participant observation as instrument. Field note was used to see their engagement in using English in the classroom. The aftereffects of this action demonstrated an expansion in excitement of the students to learn English and increment fearlessness and English talking abilities with regards to adequate vocabulary in regards to the material of telling story in sequence by using Once Upon a Time card. The results of this study are then prescribed as contribution to give Indonesian students one more involvement in speaking English.